(untitled) (Research, Society and Development, 2020)
21st century and nations and corporations aim to increase their assets through policies and measures that do not always benefit the population or the country as a whole. Embedded in the process of profit generation is the task of giving value or price to things and such a practice is a way to market products. However, it is not possible to buy or sell something that has no predefined value. Trading something involves first defining what value such merchandise has. One of the biggest marketing challenges has been in relation to the commodification of water. This paper addresses the issue of the evolution of water trade, the attempts to value and commodify it, and the little-known water market that persists in capitalizing on water through the process of valorization and commodification as if this natural resource were privately owned. from a person, company, corporation or even from the same country. The literature review also addresses the effort that large corporations are making to control this asset that should be available to all at no additional cost. Finally it is concluded that this trade is already well structured and moving billions of dollars every year however, very subtly going unnoticed by the world population.